MANIFESTASI KETIDAKADILAN GENDER DALAM CERITA RAKYAT NUSANTARA (Manifestation of Gender Inequality in the Archipelago Folktales) - Prima Hariyanto (SALINGKA, 2014)
Gender and feminism increasingly are voiced loudly by their followers and supported by some part of community. Assumption that female gender is subordinate to men seems to have its legitimacy from the public so that it weakened the position of women in society itself. This apparently has been happening for years and can be traced back to the Nusantara folktales. This research reveals gender issues in folklores that developed in Nusantara. Stories used in this study are the story from various provinces in Indonesia. This research uses descriptive methods and data collection techniques using literature analysis. The present study found a gender marginalization (5 stories), subordination (15 stories), stereotyping (19 stories), violence (30 stories), and excessive workload (12 stories).